Techno economic systems and excessive consumption: a political economy of 'pathological' gambling. (30th October 2013) - Reith, Gerda
Abstract This article argues that gambling is a paradigmatic form of consumption that captures the intensified logic at the heart of late modern capitalist societies. As well as a site of intensified consumption, it claims that gambling has also become the location of what has been described as a new form of 'social pathology' related to excess play. Drawing on Castells' (1996) notion of techno‐economic systems, it explores the ways that intersections between technology, capital and states have generated the conditions for this situation, and critiques the unequal distribution of gambling environments that result. It argues that, while the products of these systems are consumed on a global scale, the risks associated with them tend to be articulated in bio‐psychological discourses of 'pathology' which are typical of certain types of knowledge that have salience in neo‐liberal societies, and which work to conceal wider structural relationships. We argue that a deeper understanding of the political and cultural economy of gambling environments is necessary, and provide a synoptic overview of the conditions upon which gambling expansion is based. This perspective highlights parallels with the wider global economy of finance capital, as well as the significance of intensified consumption, of which gambling is an exemplary instance. It also reveals the existence of a geo‐political dispersal of 'harms', conceived as deteriorations of financial, temporal and social relationships, which disproportionately affect vulnerable social groups. From this, we urge an understanding of commercial gambling based on a critique of the wider social body of gambling environments within techno economic systems, rather than the (flawed) individual bodies within them.